A 3D-printed PRP-GelMA hydrogel promotes osteochondral regeneration through M2 macrophage polarization in a rabbit model. (1st July 2021) - Jiang, Guangyao; Li, Sihao; Yu, Kang; He, Bin; Hong, Jianqiao; Xu, Tengjing; Meng, Jiahong; Ye, Chenyi; Chen, Yazhou; Shi, Zhongli; Feng, Gang; Chen, Weishan; et al.
Abstract: Osteochondral regeneration is an orchestrated process of inflammatory immunity, host cell response, and implant degradation in tissue engineering. Here, the effects of a platelet-rich plasma (PRP)-gelatin methacryloyl (GelMA) hydrogel scaffold fabricated using the digital micro-mirror device (DMD) technique for osteochondral repair were investigated in a rabbit model. GelMA hydrogels with different PRP concentrations were fabricated, and their roles in bone marrow mesenchymal stem cells (BMSCs) and macrophage polarization in vitro were investigated. The incorporation of 20% PRP into the hydrogel showed optimal effects on the proliferation, migration, and osteogenic and chondrogenic differentiation of BMSCs. The 20% PRP-GelMA (v/v) hydrogel also promoted M2 polarization with high expression of Arg1 and CD206. Compared to the 20% PRP group, the 50% PRP group showed similar biological roles in BMSCs but less extent of osteogenesis. In the vivo study, the 20% PRP-GelMA composite was used for osteochondral reconstruction and showed more cartilage and subchondral bone regeneration than that observed using the pure GelMA hydrogel. The PRP-GelMA group exhibited more M2 macrophage infiltration and less M1 macrophage presentation at three time points as compared to the nontreatment group. The expression of Arg1 in the PRP-GelMA group increased significantly at 6 weeks but decreased to a lower level at 12 weeks, while CD163 showed sustained high expression until 18 weeks. Our findings demonstrated that the 3D-printed PRP-GelMA composite could promote osteochondral repair through immune regulation by M2 polarization and could be a potential candidate for osteochondral tissue engineering. Statement of significance: PRP-GelMA hydrogels promoted the migration and osteogenic and chondrogenic differentiation of BMSCs. PRP-GelMA hydrogels participated in immune regulation and M1-to-M2 transition of macrophages. PRP-GelMA hydrogels coordinated and promoted several overlapping osteochondral repair events, including dynamic immune regulation, chemotaxis of MSCs, and osteochondral differentiation. PRP-GelMA hydrogels showed superior cartilage and subchondral bone repair properties. Graphical abstract: Image, graphical abstract